Proposals of themes to be used in environmental education activities in interpretative trails: A case study in the Mauro Romano Ecological Park, Municipality of Vassouras, Rio de Janeiro State - Souto de Almeida, Fábio; Cunha Lemos, Mariana; Guimarães Ribeiro, Jade (Guará Journal, 2023)
This study aimed to identify topics for discussion with participants in environmental education activities on the trails of the Mauro Romano Ecological Park of the Vale Verdejante Civil Association, in the municipality of Vassouras, Rio de Janeiro state. Visits to the park were conducted to observe its characteristics and suggest approaches to points of interest for environmental education activities along the existing trails. Several interesting features were observed on the two trails studied, herein referred to as the "reforestation trail" and the "agroforestry trail," for disseminating information and discussing environmental issues, including species diversity and the importance of their protection, natural resource conservation, and agroecological practices. Furthermore, the dynamics proposed in this study will be useful for assimilating the knowledge disseminated during activities in the park.